Urban Imaginaries : Locating the Modern City - Bender, Thomas; Cinar, Alev (Book collections on Project MUSE., 2007)
"For millennia, the city stood out against the landscape, walled and compact. This concept of the city was long accepted as adequate for characterizing the urban experience. However, the nature of the city, both real and imagined, has always been more permeable than this model reveals. The essays in [this book] respond to this condition by focusing on how social and physical space is conceived as both indefinite and singular. They emphasize the ways this space is shared and thus made into urban culture. Urban Imaginaries offers case studies on cities in Brazil, Israel, Turkey, Lebanon, and India, as well as in the United States and France, and in doing so blends social, cultural, and political approaches to better understand the contemporary urban experience."--Publisher description, from page 4 of cover